Cell membrane-camouflaged nanoparticles: selection strategy in incurable disease treatment - Hyunjun Moon; Jeongeun Kim; Gyuri Bae; Woong Choi; Suk Han Jung; Soobok Lee; Kangseok Lim; Jin Hee Na; Jeong Uk Choi; Jong-Ho Kim; Sangmin Lee (Journal of Pharmaceutical Investigation, 2026)

Production and application of Paenibacillus polymyxa levan as an antiviral priming agent against cucumber mosaic virus infection in tobacco plants - Hyunjun Ko; Hangil Kim; Ji Won Heo; Sangjun Lee; Yongtae Yu; Hyebin Kim; Hyeon-Seok Oh; Chan-Gi Min; Seokmin Baek; Han Suk Choi; Sung Jin Moon; Woohyun Sim; et al. (Carbohydrate Polymers, 2025)

Non-linear long-term trend in volume transport through the Korea/Tsushima Strait - Jae-Hong Moon; Hyunjun Jang; Taekyun Kim; Hyeonsoo Cha; Naoki Hirose (Frontiers in Marine Science, 2023)
Based on the relation between volume transport and sea level difference across the Korea/Tsushima Strait (KTS), in this study, we estimated the volume transport of the Tsushima Warm Current over the past four decades and examined its long-term trend using an ensemble empirical model decomposition (EEMD) method. The estimated geostrophic transports showed very good agreement with those measured by acoustic Doppler current profiler and those estimated from satellite altimetry-based sea level data. This corroborates the reliability of the long-term estimation. EEMD analysis revealed an acceleration in volume transport in the KTS, with a persistent increase in the trend rate occurring after the mid-1980s. Further analyses indicate that the trend shift in the KTS closely coincided with an upper-ocean warming trend in the East/Japan Sea (EJS) after the mid-1980s. Analyzing large-scale wind patterns suggests that long-term trends of wind stress curls over the North Pacific are likely a key driver of the trend shifts in the inflow through the KTS and the upper-ocean warming in the EJS over the past four decades.

Label-free quantitative proteomic analysis determines changes in amino acid and carbohydrate metabolism in three cultivars of Jerusalem artichoke tubers - Cheol Woo Min; Won Yong Jung; Hyun Ji Park; Ki-Beom Moon; Hyunjun Ko; Jung-Hoon Sohn; Jae-Heung Jeon; Hyun-Soon Kim; Ravi Gupta; Sun Tae Kim; Hye Sun Cho (Plant Biotechnology Reports, 2019)